CYP2D6 polymorphisms influence the efficacy of adjuvant tamoxifen in Thai breast cancer patients - Sirachainan E; Jaruhathai S; Trachu N; Panvichian R; Sirisinha T; Ativitavas T; Ratanatharathorn V; Chamnanphon M; Sukasem C (Pharmacogenomics and Personalized Medicine, 2012)
Ekaphop Sirachainan,1 Sureerat Jaruhathai,1 Narumol Trachu,2 Ravat Panvichian,1 Thitiya Sirisinha,1 Touch Ativitavas,1 Vorachai Ratanatharathorn,1 Montri Chamnanphon,3 Chonlaphat Sukasem31Division of Medical Oncology, Department of Medicine, 2Research Center, Division of Pharmacogenomics and Personalized Medicine, Department of Pathology, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, Thailand, 3Division of Pharmacogenomics and Personalized Medicine, Department of Pathology, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok, ThailandAim: We evaluated single nucleotide polymorphisms (SNPs) of CYP2D6 to identify those that influence the efficiency of tamoxifen in adjuvant treatment of breast cancer through a matched case–control study.Methods: Peripheral blood DNA was collected from 20 patients with disease recurrence during adjuvant tamoxifen treatment and from 19 patients who had completed 5 years of tamoxifen therapy without recurrence of breast cancer. CYP2D6*4 (1846G > A; rs3892097), CYP2D6*10 (100C > T, rs1065852), and CYP2D6*5 (deletion) were genotyped. The correlation between disease-free survival (DFS) and genotype and clinical outcome were assessed using Kaplan–Meier analysis and a log-rank test.Results: We found the allelic frequency of CYP2D6*10 during this study. Patients with the CYP2D6*10 homozygous variant T/T genotype had a significantly shorter median of DFS than those with C/T (P = 0.036), but DFS was not significantly different from that of patients with the C/C genotype (P = 0.316). One patient who was a carrier both of CYP2D6 G/A (1846G > A) and T/T (100C > T) had DFS of 22.7 months.Conclusions: This study demonstrated that CYP2D6*10/*10 was significantly associated with shorter DFS in Thai breast cancer patients receiving tamoxifen. This was a pilot study investigating the correlation of CYP2D6 polymorphisms and their influence on clinical outcomes in Thai estrogen receptor-positive breast cancer patients.Keywords: breast cancer, CYP2D6 polymorphism, pharmacogenetics, single-nucleotide polymorphism (SNP), tamoxifen